Kigezi (Südwest-Uganda) - Manshard, Walther (ERDKUNDE, 1965)
This paper, which is based on field-work undertaken in Uganda in August-September 1963, attempts to outline the agricultural geography of Kigezi, the mountain region in the southwest corner of Uganda. Although the higlands of Kigezi were visited in recent years by an increasing number of Europeans, mainly on account of the cooler climate, little or no work has been done on its geography. In the field of agricultural science one has to rely mainly on the publications of Purseglove and Byagagaire, who have concentrated their attention especially on resettlement questions. The following essay opens with a sketch of the structure and history of people and settlement in the area concern ed, because the natural pattern of regional structure has been greatly influenced by a comparatively dense population. Accounts of land-use systems, agricultural production for subsistence and export, live-stock farming, labour supply, and land-tenure of the region follow. The important problem of resettlement, such an urgent policy matter in many tropical countries, is described on the basis of Kigezi experience in the last decades. In this connection also the recent influx of refugees after the exodus of many Tutsi from Rwanda is of a general interest. Finally, the position of Kigezi within the political frame-work of the wider East African scene is analysed in time and space.